The Effect of Access Cavity Preparation, Canal Shaping and Pericervical Dentine Preservation on the Fracture Resistance of Endodontically Treated Mandibular Molars - van der Vyver, Peet (University of Pretoria, 2023)
Thesis (PhD (Dentistry))--University of Pretoria, 2023.